Loan loss provisioning practices of Asian banks - Packer, Frank; Zhu, Haibin (BIS working papers, 2012)
In the wake of the Asian financial crisis, many regimes in Asia adopted stricter provisioning requirements, as well as discretionary measures, with the objective of increasing provisioning in good times in response to rising levels of risk. Based on a final sample of 240 banks in 12 Asian economies, the evidence is that countercyclical loan loss provisioning has dominated throughout emerging Asia, most strikingly so in the case of India. Thus, loan loss provisioning did not simply become more conservative at all points in time subsequent to the Asian financial crisis, but actively leaned in a fashion that ameliorated swings in earnings and the macroeconomy.